Analysis of Risk Factors for Violence Against Pregnant Women Using a QR Code Survey: A Cross-sectional Study - Sesaria Lukman; Mohammad Hakimi; Islamiyatur Rokhmah (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2026)
Violence against pregnant women has serious physical, psychological, and social consequences for both mothers and their unborn children. The World Health Organization (WHO, 2024) reports that one in three women experience violence, yet many cases remain undetected because of reporting barriers, stigma, and limited screening methods. This study aimed to identify the risk factors associated with violence against pregnant women by utilizing QR Code technology as a secure survey tool in the working area of the Yogyakarta City Health Office. A cross-sectional study was conducted among 463 pregnant women using a validated and reliable questionnaire. The prevalence of violence was 36.3%, with psychological violence identified as the most common form. Logistic regression analysis showed that young maternal age (OR = 2.11; p = 0.010), low income (OR = 1.79; p = 0.015), unwanted pregnancy (OR = 2.69; p < 0.001), and a history of previous violence (OR = 4.05; p < 0.001) were significant predictors. Strengthening routine screening and community-based prevention programs is recommended.